Experimental Wing Damage Affects Foraging Effort and Foraging Distance in Honeybees Apis mellifera - Andrew D. Higginson; Christopher J. Barnard; Adam Tofilski; Luis Medina; Francis Ratnieks (Psyche: A Journal of Entomology)
Bees acquire wing damage as they age, and loss of wing area affects longevity and behaviour. This may influence colony performance via effects on worker behaviour. The effects of experimental wing damage were studied in worker honeybees in observation hives by recording survivorship, how often and for how long bees foraged, and by decoding waggle dances. Mortality rate increased with both age and wing damage. Damaged bees carried out shorter and/or less frequent foraging trips, foraged closer to the hive, and reported the profitability of flower patches to be lower than did controls. These results suggest that wing damage caused a reduction in foraging ability, and that damaged bees adjusted their foraging behaviour accordingly. Furthermore, the results suggest that wing damage affects the profitability of nectar sources. These results have implications for the colony dynamics and foraging efficiency in honeybees.